Germinated and Lactic Fermented Soybean Seeds, a Natural Alternative for Healthy Bones. A Scientific Approach - Gratziela Victoria BAHACIU (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2018)
Combining the consumers interests in healthy eating with technology evolution, scientists can increase the food nutritional value by biotechnology. Soybean minerals have lower bioavailability due to phytates, which are hydrolysed by activated phytase during germination. The purpose of this paper is to investigate the relation between soybean seeds germination (4 days at 25°C) and lactic fermentation (24, 48, 72 or 96 hours by immersing soybeans into a medium with Lactobacillus (0.8x108CFU/ml), supplemented with 1, 3 and 5% saccharose). The minerals bioavailability, calculated as mineral extractability in a 0.03M HCl solution. We observed that germination at 25°C for 4 days increased the level of soluble minerals with 48.76% Ca, 22.31% Fe, 15.77% Mg and 28.04% Zn, respectively, compared to control samples. Combining germination with lactic fermentation, the level of soluble minerals increased compared to germinated ones: Ca, 53.4%, Fe, 59.56%, Mg, 43.41% and Zn, 40.87% respectively. Combining germination with lactic fermentation meets the need of consumers for bio, healthy food products offering a good source of minerals. The best processing conditions for obtaining the optimum level of available minerals was germination for 4 days at 25°C followed by fermentation for 72 hours into a lactic bacteria medium containing 3% added saccharose.